In silico Structure–Based Investigation of Key Residues of Insecticidal Activity of Sip1Aa Protein - Wang, Jing; Ding, Ming-Yue; Wang, Jian; Liu, Rong-Mei; Li, Hai-Tao; Gao, Ji-Guo (Frontiers in Microbiology, 2020)
Colaphellus bowringi Baly mainly damages cruciferous vegetables, leading to huge economic losses. The secretory insecticidal protein (Sip) of Bacillus thuringiensis (Bt) has high insecticidal activity against Colaphellus bowringi Baly. The tertiary structure of Sip1Aa protein was analyzed by homologous modeling and other bioinformatics methods to predict the conserved domain of Sip1Aa protein. Acidic and basic amino acids in the conserved domain were selected, and alanine was used to replace these amino acids by site-directed mutation. The difference between the insecticidal activities of mutant protein and Sip1Aa protein was analyzed. The insecticidal activities of H99A, K109A, K128A and E130A against the Colaphellus bowringi Baly were significantly increased, among which that of K128A was the most obviously changed, the LC50 value was decreased by about ten times compared with that of Sip1Aa protein. The LC50 value of mutant E130A was 0.286 ug/mL, which was about six times less than that of Sip1Aa. K128 and E130 were both in the β9-β10 loop. The toxicity of D290A, H242A and H303A to the Colaphellus bowringi Baly was significantly reduced, and their LC50 value increased by about six, eight and three times compared with that of Sip1Aa protein, respectively. This study showed that acidic and basic amino acid residues played a certain role in the toxicity of Sip1Aa protein, and the loss of side chains in key residues had a significant impact on the insecticidal activity of the protein. This study provides the theoretical basis for revealing the relationship between the structure and function of Sip1Aa protein, and also provides a new method for the subsequent study of sip gene.